Antiretroviral exposure during pregnancy and adverse outcomes in HIV-exposed uninfected infants and children using a trigger-based design. (2nd January 2016) - Williams, Paige L.; Hazra, Rohan; Van Dyke, Russell B.; Yildirim, Cenk; Crain, Marilyn J.; Seage, George R.; Civitello, Lucy; Ellis, Angela; Butler, Laurie; Rich, Kenneth
Abstract : Objective: To evaluate the safety of in-utero antiretroviral exposure in children born to mothers with HIV, using a trigger-based design. Design: The Surveillance Monitoring of ART Toxicities Study is a prospective cohort study conducted at 22 US sites to evaluate safety of in-utero antiretroviral drug exposure in HIV-uninfected children born to HIV-infected mothers. Children meeting predefined clinical or laboratory thresholds have more intensive evaluations to determine whether they meet criteria for adverse events. Methods: Adverse event "cases" were defined for the following domains: growth, hearing, language, neurology, neurodevelopment, metabolic, hematologic/clinical chemistry and blood lactate. We used adjusted log-binomial models to calculate relative risks (RR) of case status overall and within individual domains for various antiretroviral exposures during pregnancy. Results: Among 2680 youth enrolled between 2007 and 2012 (48% female, 66% black, 33% Hispanic), 48% met a trigger and 25% were defined as a case in at least one domain. Language (13.2%) and metabolic (11.4%) cases were most common. After adjustment for birth cohort and other factors, there was no association of any antiretroviral regimen, drug class, or individual drug with meeting overall case criteria (case in any domain). Within individual domains, zidovudine (74% exposed) was associated with increased risk of metabolic case [RR = 1.69, 95%confidence interval (CI) 1.08–2.64] and didanosine plus stavudine (<1% exposed) with increased risk of both neurodevelopmental (RR = 12.40, 95%CI 5.29–29.08) and language (RR = 4.84, 95%CI 1.14–20.51) cases. Conclusion: Our findings support current recommendations for combination antiretroviral therapy during pregnancy, although higher risk of metabolic disorder with zidovudine exposure warrants further study. Abstract : Supplemental Digital Content is available in the text